China motorization trends: New directions for crowded cities - Ng, Wei-Shiuen; Schipper, Lee; Chen, Yang (Journal of Transport and Land Use, 2010)
This paper examines two major emerging constraints on transport in fast-growing Chinese urban cities: oil supply and urban infrastructure. The research considers automobile technology, alternative fuels, and mobility choices, as well as policy measures that could be adopted to reduce the use of oil for transport and greenhouse gas emissions. Three transport energy scenarios, “Road Ahead,” “Oil Saved,” and “Integrated Transport,” illustrate potential motorization trends given different policy, vehicle technology, alternative fuels, and driving-behavior assumptions. In the Integrated Transport scenario, where congestion and space constraints favor small and vehicles moving at slower speeds, gasoline and electric cars are the highest in use. Oil consumption in the Integrated Transport scenario is only 12 percent of its value in Road Ahead by 2020, while carbon emission is 79 percent lower. Policies such as vehicle technology and fuel requirements, while important, are not as crucial as integrated land use development, taxation of vehicle use, road pricing, and the prioritization of public and non-motorized transport that could trigger a world of fewer, smaller and more efficient cars. According to experiences around the world, fuel and carbon dioxide concerns alone are not strong enough to promote a change in the path of individual motorization.